2023
DOI: 10.3390/medicina59040805
|View full text |Cite
|
Sign up to set email alerts
|

Should Procalcitonin Be Included in Acute Cholecystitis Guidelines? A Systematic Review

Abstract: Background and Objectives: Acute cholecystitis (AC) is a common surgical emergency. Recent evidence suggests that serum procalcitonin (PCT) is superior to leukocytosis and serum C-reactive protein in the diagnosis and severity stratification of acute infections. This review evaluates the role of PCT in AC diagnosis, severity stratification, and management. Materials and Methods: PubMed, Embase, and Scopus were searched from inception till 21 August 2022 for studies reporting the role of PCT in AC. A qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Several studies found CRP to be a good predictive factor for conversion; however, the cut-off values varied widely from 76 mg/L to 220 mg/L [5,[10][11][12][13]. Together with the valuable findings provided by ultrasound and CT exam, specific biomarkers were analyzed for the possible predictive role for the severity of local inflammation, such as the YKL-40 protein level [14], serum level of visfatin [15], procalcitonin [16], human neutrophil lipocalin [17], chitotriosidase, and neopterin [18]. However, their availability in emergencies is limited in many surgical departments.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found CRP to be a good predictive factor for conversion; however, the cut-off values varied widely from 76 mg/L to 220 mg/L [5,[10][11][12][13]. Together with the valuable findings provided by ultrasound and CT exam, specific biomarkers were analyzed for the possible predictive role for the severity of local inflammation, such as the YKL-40 protein level [14], serum level of visfatin [15], procalcitonin [16], human neutrophil lipocalin [17], chitotriosidase, and neopterin [18]. However, their availability in emergencies is limited in many surgical departments.…”
Section: Introductionmentioning
confidence: 99%
“…Only one patient had a PCT measurement, which was 83.86 ng/mL. It would be interesting to assess whether PCT is more sensitive in emphysematous hepatitis, as observed in hepatobiliary infections [ 16 ]. The diagnosis was based on a CT scan, sometimes associated with an ultrasound exam.…”
Section: Resultsmentioning
confidence: 99%